ECONOMIC VALUE ADDED ASSESSMENT APPLIED TO THE PORTUGUESE SME DURING THE CRISIS PERIOD - Oliveira, L.; Inácio, P.; Oliveira, C. (10th Portuguese Finance Network Conference, 2018)
How do companies know that they are staying in course? How can managers make sure their efforts are, indeed, being directed towars value creation? The measurement of a company’s performance is the only way to assure the ultimate company’s purpose is being achieved, which is to create value for its shareholders. In this article we investigate the behavior of best 315 Portuguese small and medium companies (SMEs) from 2007 until 2010, to answer two central questions: “Did the largest and best Portuguese SMEs create value during the international crisis period?" and “Which sectors have contributed most to the value creation in those years?”. The findings indicate that globally the companies have not created value for their shareholders. Nevertheless, “Electrical Equipment” and “Commercial Services and Supplies” were the only two sectors that contributed, with a positive MVA, to this globally negative scenario.